Comparison of penile block using the reverse US-guided nerve block or landmark guidance during circumcision in pediatric population: a retrospective study - Christophel-Plathier, E.; Saucy, T.; Mauron, S. (Frontiers in Anesthesiology, 2024)
Dorsal penile nerve block (DPNB) using anatomical landmarks remains the technique of choice for analgesia during circumcision. Ultrasound guidance has been shown to be safer and more effective. However, a recent study reported no differences between US-DPNB and DPNB in terms of analgesia. Thus, reverse US dorsal penile nerve block (RUS-PNB) has been developed, which is the image mirror of US-DPNB.Comparison between RUS-PNB and DPNB in terms of efficacy, safety, and speed of execution.This is a single-center retrospective study. Patients were all males, aged <16 years who underwent circumcision between 1 November 2019 and 31 December 2020. Exclusion criteria were undergoing another surgical procedure during the same operation, not undergoing a block, or refusing to participate.All patients received bupivacaine 0.5% using either DPNB or RUS-PNB.Data including demographic background information, doses of opioids used converted into an equivalent morphine dose per kilogram, different times taken for various medical acts, and complications were collected.A total of 139 patients were included. 45 (Group 1) underwent DPNB and 94 (group 2) underwent RUS-PNB.There were no differences in age, weight, height, or ASA scores between the groups.The per-operative morphine equivalent dose was Group 1; mean 0.5 mg/kg ± 0.2, Group 2; mean 0.2 mg/kg ± 0.2, with p < 0.001.The mean postoperative morphine equivalent dose, duration of anesthesia, and surgery were similar.The volume required was higher for Group 2; median 0.3 ml/kg than for Group 1; median 0.2 ml/kg. There were no complication, although two instances failure of block failures (4.7%) were observed in group 1 and three (3.3%) in group 2 (p= 0.653). This was due to the need for additional opioids during surgery.The RUS-PNB technique is more efficient than the traditional DPNB method and does not require a longer procedure. It is likely that the incidence of complications is lower when the RUS-DPNB technique is employed, as the injection is performed "under vision" in contrast to the landmark method, which is carried out "blindly" as it results in fewer complications.